Kesembronoan dan Memain-mainkan Muka dalam Debat Cagub dan Cawagub Aceh Periode 2025-2030 - Miranda, Cut; Rahayu, Ririn; Ginting, Reza Pahlevi (FKIP Universitas Palangka Raya, 2025)
The purpose of this study is (1) to describe the forms of language impoliteness in the category of gratuitous in the debate of the Aceh gubernatorial and deputy gubernatorial candidates for the 2025-2030 period, and (2) to describe the forms of language impoliteness in the category of face aggravating mockery in the debate of the Aceh gubernatorial and deputy gubernatorial candidates for the 2025-2030 period. The data in this study are utterances containing gratuitous and face aggravating mockery in speech (impoliteness) in the debate of the Aceh gubernatorial and deputy gubernatorial candidates for the 2025-2030 period. The data source in this study is the video of the debate of the Aceh gubernatorial and deputy gubernatorial candidates for the 2025-2030 period in the first and second debates. Data collection in this study included (1) documenting data obtained from the Kompas Aceh YouTube channel (downloading debate videos and screen recordings), (2) observing and paying attention to word choice and speech patterns in the Aceh gubernatorial and vice gubernatorial debate for the 2025-2030 period, and (3) recording important and relevant data for the analysis. The data analysis technique used in this study was Miles and Huberman's theory, which includes data reduction, data presentation, and conclusion drawing. Based on the research results, of the two categories of impoliteness, the category of gratuitous was more dominant than face aggravating mockery. There were 16 data items in the gratuitous category and 9 items in the face aggravating category in the Aceh gubernatorial and vice gubernatorial debate for the 2025-2030 period.